DECENTRALIZATION PROCESS AND FINANCIAL AUTONOMY OF LOCAL GOVERNMENT UNITS IN ALBANIA - Hoxhaj, Entela (European Scientific Journal, ESJ, 2014)
The purpose of this paper is to give a general overview on the decentralization process and on the financial autonomy of local government units in Albania. The principal base for the analysis done is the legal framework, accompanied shortly with examples of its implementation in several communes or municipalities. The paper is organised in 3 issues, which treat respectively the organization of local government in Albania, decentralization of functions and responsibilities in favour of the units of local government, and their budget and resources of financing. There has been some difficulties in practice during decentralization process raised out when fulfilling the whole legal framework on exercising exclusive and shared competences of local units of government, because of the dependence by the respective institutions for the implementation of legal acts for exclusive and shared functions in the fields of education, economic support and health care, and by lack of funds of the responsible ministry to transfer the service of water supply. In Albania seems yet early to give right importance to regions, and especially with regard to the aspirations for European integration many challenges raise to the Albanian institutions.